ANALISIS MARGIN PEMASARAN TOMAT DI DESA KOPIWANGKER KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA (Marketing Margin Analysis of Tomato in the Village of Kopiwangker District of West Langowan in Minahasa Regency) - Hendra Alang; Celcius Talumingan; Grace A.J. Rumagit (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2019)
The objective of this research was to determine the pattern of tomato marketing channels, to calculate the costs, profits and marketing margins of tomatoes and to analyze the farmer's share in each tomato marketing channel in Kopiwangker Village. This research was conducted for 3 (three) months, from April to June 2019. Sampling method is done by purposive sampling Data used in this study are primary and secondary data. Data collected and analyzed descriptively where the data collected will be presented in tabular form and to know the marketing margins and marketing costs at the marketing agency level in the marketing channel used quantitative analysis by calculating the cost, profit and marketing margin. Based on the research results of Tomato Marketing Margin Analysis in Kopiwangker Village, West Langowan Subdistrict, Minahasa Regency, it can be concluded as follows: Kopiwangker Village has 2 marketing channels, namely marketing channel I, farmers to retailers in Langowan market, and marketing channel II, farmers, collectors and retailers in the Karombasan market. Marketing channel I total costs Rp. 139.8, profit of Rp 415.2 / kg and marketing margin of Rp. 555. Marketing channel II costs a total of Rp 301.2 / kg, profit 377.3 and marketing margin Rp 679, the farmer share in marketing channel I is 78.28% and marketing channel II is 72.36%.Keywords: Margins, Marketing, Kopiwangker Village